Vapor growth of mercuric iodide tetragonal prismatic crystals - Ariesanti, Elsa (Kansas State University, 2013)
The effect of polyethylene addition on the growth of mercuric iodide (HgI[supscript]2) tetragonal prismatic crystals is examined. Three types of polyethylene powder are utilized: low molecular weight (¯Mw ~ 4 x 103), ultra high molecular weight (¯Mw ~ 3 x 6 106), and spectrophotometric grade polyethylenes. Among these types of polyethylene, the low molecular weight polyethylene produces the most significant change in HgI[supscript]2 morphology, with {110} being the most prominent crystal faces. Thermal desorption - gas chromatography/mass spectroscopy (TD-GC/MS) studies show that thermal desorption of the low molecular weight polyethylene at 100°C and 150°C produce isomers of alkynes, odd nalkanes, and methyl (even-n) alkyl ketones. HgI[supscript]2 growth runs with n-alkanes, with either neicosane, n-tetracosane, or n-hexatriacontane, cannot replicate the crystal shapes produced during growth with the low molecular weight polyethylene, whereas HgI[supscript]2 growth runs with ketones, with either 3-hexadecanone or 14-heptacosanone, produce HgI[supscript]2 tetragonal prismatic crystals, similar to the crystals grown with the low molecular weight polyethylene. C-O double bond contained in any ketone is a polar bond and this polar bond may be attracted to the mercury atoms on the top-most layer of the {110} faces through dipoledipole interaction. As a result, the growth of the {110} faces is impeded, with the crystals elongated in the [001] direction and bounded by the {001} faces along with large, prismatic {110} faces.
Keywords: Mercuric iodide; Vapor growth; Horizontal furnace; Faile method; Materials Science (0794); Nuclear Engineering (0552)